Multiparametric Cardiac Magnetic Resonance Imaging of Cardiac Involvement Associated With Sporadic Inclusion Body Myositis. (December 2021) - Hayashi, Hidetaka; Oda, Seitaro; Kidoh, Masafumi; Jyo, Aki; Kobayashi, Naoki; Okada, Yujiro; Matsubara, Soichiro; Ueda, Mitsuharu; Hirai, Toshinori
Abstract : Supplemental Digital Content is available in the text.